MBD4 deficiency is predictive of response to immune checkpoint inhibitors in metastatic uveal melanoma patients. (September 2022) - Saint-Ghislain, Mathilde; Derrien, Anne-Céline; Geoffrois, Lionnel; Gastaud, Lauris; Lesimple, Thierry; Negrier, Sylvie; Penel, Nicolas; Kurtz, Jean-Emmanuel; Le Corre, Yannick; Dutriaux, Caroline; Gardrat, Sophie; Barnhill, Raymond; et al.
Abstract: Background: MBD4 mutations have been reported in uveal melanomas, acute myeloid leukemias, colorectal adenocarcinomas, gliomas, and spiradenocarcinomas and cause a hypermutated phenotype. Although metastatic uveal melanomas (mUM) are usually resistant to immune checkpoint inhibitors (ICI), the first reported MBD4 -mutated (MBD4m) patient responded to ICI, suggesting that MBD4 mutation may predict response to ICI. Methods: Retrospective cohort of mUM patients treated with ICI. MBD4 was sequenced in a subset of these patients. Results: Three hundred mUM patients were included. Median follow-up was 17.3 months. Ten patients with an objective response and 20 cases with stable disease for >12 months were observed, corresponding to an objective response rate of 3.3% and a clinical benefit ( i.e., responder patients and stable disease) rate of 10%. Of the 131 tumors sequenced for MBD4, five (3.8%) were mutated. MBD4 mutation was associated with a better objective response rate as three out of five MBD4m versus 4% of MBD4 wild-type patients responded (p < 0.001). Of these five responders, three presented progressive disease at 2.8, 13.9, and 22.3 months. Median PFS was 4.0 months in MBD4 wild-type and 22.3 months in MBD4m patients (HR = 0.22; p = 0.01). Median OS in MBD4def patients was unreached as compared to 16.6 months in MBD4pro (HR = 0.11; 95% CI: 0.02–0.86; log-rank p-test = 0.04; Fig. 2e). Conclusions: In mUM patients, MBD4 mutation is highly predictive for the response, PFS, and overall survival benefit to ICI. MBD4 could be a tissue-agnostic biomarker and should be sequenced in mUM, and other tumor types where MBD4 mutations are reported. Graphical abstract: Image 1 Highlights: All-comer metastatic UM show a response rate of 3.3% to ICI. MBD4 mutations are present in 3.8% of metastatic UM patients. MBD4 mutation predicts response to ICI (60% versus 4% in wild type; p < 0.001). MBD4 m predicts PFS benefit to ICI (median of 22.3 versus 4.0 months; p = 0.01). MBD4 m predicts OS benefit to ICI (unreached median versus 16.6 months; p = 0.004).